Reduction of soot emission from diesel fuelled engine using a novel diesel particulate filter - M.M., Taib; Ahmad Jais, Alimin; S.H., Amirnordin; Hamimah, Abd. Rahman; Mas Fawzi, Mohd Ali (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.